Evaluation and Implementation of Green Building in Office Building (Case Study: Munara 99 Sabilulungan Building) - Rina Marina Masri; Iskandar Muda Purwaamijaya; Veily Vitada; Alya Sekar Hapsari (School of Postgraduate Studies, Diponegoro Univer, 2024)
Green Building concept is the concept of building planning to fulfill a better life for the next generation. A building can be classified as a green building if it meets the requirements and has green building certification. The purpose of this research is to analyze and evaluate the existing building criteria, namely the Munara 99 Sabilulungan building through the calculation of Greenship GBCI v1.2 assessment points because there is no green building assessment and rating from GBCI so that an evaluation of green building assessment is needed. A descriptive method with an evaluative approach was chosen to describe and compare the existing condition of the building with the greenship assessment tool for new buildings v1.2. The GBCI greenship assessment for new buildings v1.2 consists of 6 categories, namely land use suitability, energy efficiency and conservation, water conservation, material sources and cycles, space health and comfort, and building environmental management. To support the GBCI greenship assessment, the data used are building shop drawings, Bill of Quantity (Boq), interview results and field observations. Based on the results of the green building assessment, the Munara 99 Sabilulungan building received a GBCI bronze rating with a score of 44 points. To improve the green building rating to a gold rating, the Munara 99 Sabilulungan building is recommended to improve several categories so that it can get a gold rating with a value of 67 points and for improvements to increase the rating requires a cost of Rp 1,790,085,000, -.